2021
DOI: 10.3991/ijet.v16i11.22303
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Using the Differentiated Instruction (DI) Strategy on Student Achievement in an Intermediate Stage Science Course

Abstract: This study aimed to investigate the impact of using the differentiated instruction strategy on stu-dents ’achievement in an intermediate school course and their attitudes towards it. The study was conducted using a semi-experimental method. Participants were 483 students, split into two groups: empiric (n = 244) and control (n = 239). Achievement tests and questionnaires were used as tools for this study. Data analyzed through the SPSS program. The results indicated that there were statistically significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Differentiated learning is an effort to adjust the learning process in the classroom in order to achieve the learning needs of each student. Through this differentiated learning, it is hoped that it can meet learning needs and develop students' creative potential so that students can solve problems and be able to think critically (Alsalhi et al, 2021;Hadi et al, 2022). This follows the results of interviews conducted with grade 4 teachers at SD N 2 Walen, which showed that this differentiated learning is carried out to meet the various needs of different students by referring to aspects of student interest, readiness and abilities possessed by students.…”
Section: Discussionsupporting
confidence: 60%
“…Differentiated learning is an effort to adjust the learning process in the classroom in order to achieve the learning needs of each student. Through this differentiated learning, it is hoped that it can meet learning needs and develop students' creative potential so that students can solve problems and be able to think critically (Alsalhi et al, 2021;Hadi et al, 2022). This follows the results of interviews conducted with grade 4 teachers at SD N 2 Walen, which showed that this differentiated learning is carried out to meet the various needs of different students by referring to aspects of student interest, readiness and abilities possessed by students.…”
Section: Discussionsupporting
confidence: 60%
“…The results indicated that there were statistically significant differences between the groups for the benefit of the empiric group that taught via DI. The results also revealed positive attitudes towards the strategy used (Alsalhi et al, 2021). It is also supported by another researcher investigating the effectiveness of Differentiated Instruction (DI) in improving reading comprehension skills in the EFL secondary stage in Bahrain (Saleh, 2021).…”
Section: The Implementation Of Teaching English Using Differentiated ...supporting
confidence: 63%
“…There are several reasons why DI is successful in increasing student achievement. First, implementing DI helps students learn and achieve learning objectives based on their ability level so that the learning process does not burden students (Alsalhi et al, 2021). In other words, differentiated learning fulfills students' needs so that they can learn better (Dorfberger & Eyal, 2023;Gheyssens, Consuegra, Engels, & Struyven, 2021;Pozas, Letzel-Alt, & Schwab, 2023).…”
Section: Effect Sizementioning
confidence: 99%